STUDI EKSPERIMENTAL PENGARUH PENAMBAHAN ADMIXTURE BETONMIX DENGAN MENGGUNAKAN SEMEN PPC TERHADAP KUAT TEKAN BETON - Nauly, Sondy Putra; Mungok, Chrisna Djaya; Handalan, Cek Putra (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2016)
As it grows concrete in building construction are often used as a structure and can be used for other things. In the process of mixing concrete on the ground frequently arise in the form of stirring and casting a result of a reduction in the amount of water usage to improve the quality of concrete, it is necessary to use additive (additive) as a mixture of concrete mix so that more plastic that will facilitate and speed up concrete hardening foundry. In this study, using a mix concrete admixture materials Betonmix, which is expected to improve the quality of the concrete compressive strength, tensile strength and modulus of elasticity sides in general and in particular to determine the change in temperature after casting, hardening time / setting time, shrinkage and porosity. Betonmix is a colorless liquid that is highly useful for improving the quality of the concrete, thus simplifying construction and produce high-quality concrete. Tests conducted on the study include compressive strength, tensile strength and modulus of elasticity sides, as well as testing the temperature after casting, hardening time test / setting time by means of Vicat, shrinkage testing using a ruler and porosity testing. For testing compressive strength, tensile strength and modulus of elasticity sides using cylindrical test specimen with a diameter of 15 cm and 30 cm high. The test specimen consists of 85 cylinders for each - each variation. This study uses five variations, normal concrete (N), normal concrete plus betonmix 1% (B1%), normal concrete plus betonmix 2% (B2%), normal concrete plus betonmix 3% (B3%) and normal concrete plus betonmix 4 % (B4%). Results of testing the temperature after casting temperature rise by 1-3oC. The test results hardening time / setting time can take an average time of hardening of concrete during the 225 minutes. From the test results of concrete shrinkage that occurs Â± 0.1 cm. The test results show that the porosity by using betonmix can reduce porosity. Testing of compressive strength, tensile strength and modulus of elasticity sides obtained optimum value on the plus concrete admixture betonmix. In the compressive strength increased by 14% compared to normal concrete (N), while the tensile strength sides an increase of 30.43% compared to normal concrete (N), and the modulus of elasticity of an increase of 32.37% compared to normal concrete (N ). Keywords :Betonmix, temperature, setting time, shrinkage, porosity, compressive strength, split tensile strength, modulus of elasticity.